Impact of feed-in generation in market prices and calibration of a capacity term to pay to traditional generation - Application to the Iberian market - Adelino J. C. Pereira (2014)
In this paper we describe the models and the simulations that were conducted in order to access the impact of feed-in subsidized generation in the market price in Portugal in the context of the Iberian Electricity Market. In Portugal and Spain feed-in generation (namely wind power) has a large share both in terms of installed capacity and generated energy and the presence of this energy in the hourly balance originates the reduction of the market price and of the number of hours during which traditional generation (namely coal and CCGT stations) are scheduled. This paper aims at evaluating this impact both in the short term (using the real market curves) and in the long term (using a long term generation expansion planning model). The paper includes results for the Iberian power system currently having a total installed capacity above 120 GW and a total demand of 310 TWh by the end of 2013.